2021
DOI: 10.1039/d1na00213a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally activated TiO2 nanoparticles with a C-dot/g-C3N4 heterostructure for photocatalytic enhancement

Abstract: Dye degradation via photocatalysis technology has been investigated intensively to tackle environmental issues and energy crisis concerns. In this work, a newly designed ternary photocatalyst was facile prepared by a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…However, because of its large band gap (∼3.2 eV), TiO 2 only absorbs the sunlight in the UV region (<400 nm, 5% of the solar energy), which largely limits its potential commercial use for waste dye degradation. 2,9 To boost the photocatalytic activity of the TiO 2 , researchers have modified TiO 2 with other types of semiconductors or use of other types of semiconductors with narrow band gaps, which can either improve the absorption of the composite or enhance the charge separation. 10−12 For example, Bayat et al reported graphene quantum dot-decorated rutile TiO 2 nanoflowers for water splitting with enhanced photocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of its large band gap (∼3.2 eV), TiO 2 only absorbs the sunlight in the UV region (<400 nm, 5% of the solar energy), which largely limits its potential commercial use for waste dye degradation. 2,9 To boost the photocatalytic activity of the TiO 2 , researchers have modified TiO 2 with other types of semiconductors or use of other types of semiconductors with narrow band gaps, which can either improve the absorption of the composite or enhance the charge separation. 10−12 For example, Bayat et al reported graphene quantum dot-decorated rutile TiO 2 nanoflowers for water splitting with enhanced photocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the composite significantly enhanced photodegradation activity toward organic dyes RhB and MB. 17 Fang et al proposed the composite formed by graphitic carbon nitride/carbon nanodots doped with ferrous ions. They reported that the composite could significantly improve the organic dye removal efficiency under the Haber−Weiss reaction conditions to promote the generation of • OH and HO 2 • (eqs 2 and3).…”
Section: Introductionmentioning
confidence: 99%
“…prepared the composite formed by g-C 3 N 4 /CDs doped with metal oxides. They demonstrated that the composite significantly enhanced photodegradation activity toward organic dyes RhB and MB . Fang et al proposed the composite formed by graphitic carbon nitride/carbon nanodots doped with ferrous ions.…”
Section: Introductionmentioning
confidence: 99%
“…Now, it is important to compare the achieved photocurrent with those present in the literature. Chen et al reported a nanocomposite consisting of TiO 2 and C-dot/g-C 3 N 4 shows a maximum photocurrent density of 1.2 μA cm –2 . A ZnO/ZnSnO 3 /C-dot heterojunction has been developed with a maximum photocurrent density of 2.2 μA cm –2 by Nguyen et al…”
Section: Resultsmentioning
confidence: 99%